Rethinking Institutionalized Impunity Through Wildlife Trafficking Case in Indonesia - Vania Lutfi Safira Erlangga; Tatag Nasrul Andriawan (Fakultas Hukum Universitas Islam Indonesia, 2026)
Impunity in Indonesia has often been examined through its physical expressions like State violence. This study broaden the concept of impunity as a structural condition that produces non-physical harm, such as the degradation of ecosystems and the erosion of community life. Using a conceptual, historical–legal, and case approach, this normative research traces how institutionalized impunity within the security apparatus (TNI and Polri) shapes environmental law enforcement and enables state actors’ involvement in illegal wildlife trafficking (IWT). Through the 2024 Asahan pangolin-scales case, where military and police personnel received lenient or delayed prosecution compared to civilian defendants, the paper exposes the mechanisms through which impunity distorts justice and accelerates environmental destruction. By reconstructing ecological and social transformations before and after wildlife extraction, the study shows how IWT undermines local ecological balance, alters community livelihoods, and entrenches asymmetrical power relations. Drawing on John H. Knox’s framework on the human right to a clean, healthy, and sustainable environment, Paul Gordon Lauren’s critique of sovereignty as a barrier to accountability, and Lawrence M. Friedman’s theory to evaluate the defective legal enforcement, this paper argues that impunity-driven environmental degradation constitutes a violation of human rights. It situates this argument within Indonesia’s legal and historical context, bridging environmental law, human rights theory, and state accountability. The analysis demonstrates that environmental harm, when enabled by institutional impunity, is not merely ecological damage but a juridical failure that endangers fundamental rights and the moral legitimacy of law itself.